Inquérito soroepidemiológico da doença de Chagas no município de Limoeiro do Norte, Ceará em 2013 - Freitas, Erlane Chaves (2014)
Chagas disease (CD) is considered neglected in many aspects, among them, for being a disease that affects people of low socioeconomic status, for the lack of investment in research to characterize the real picture of its prevalence and for the limited effectiveness of available drugs. The present study evaluated the seroprevalence of T. cruzi infection and the sociodemographic profile of people living in the city of Limoeiro do Norte - CE in the period from April to November, 2013. The seroepidemiological study was conducted in 812 randomly selected individuals including local people of both sexes, aged at least 2 years. To meet the objectives, we used the ELISA test for IgG anti-Trypanosoma cruzi antibodies and a semi-structured questionnaire to find the sociodemographic profile. Questionnaire variables were analyzed using the chi-square or Fisher exact test. From the 812 individuals anlyzed, 4.2% (34) were seropositive for CD. The following sociodemographic variables were significantly associated with seropositivity for CD: age greater than 50 years (OR = 27.6, CI = 6.66 to 114.4, p = 0.000); incomplete primary education (PR = 5, 15 CI = 1.83 to 14.47, p = 0.000) and retired occupation (PR = 7.25, CI = 3.72 to 14.14, p = 0.000). The current housing conditions of the participants diagnosed with Chagas disease were similar to those uninfected. Seropositivity for CD was 6.17 times higher in the group of those who have lived in mud houses (CI = 2.19 to 17.37). There was no vertical transmission in the subjects studied, since none of the participants with Chagas-infected mother was reactive for anti-T. cruzi. There was no association between transfusions and seropositivity, indicating that vectorial transmission possibly occurred in this area. Among individuals infected with T. cruzi, most reported having at least one health problem (p = 0.000), and hypertension was the only comorbidity out of those cited that showed association with CD (p = 0.000). There was a significant predominance of seropositivity among those individuals that go to the doctor more than twice a year (p = 0.000) and perform some kind of test frequently (p = 0.025). This study brought us the seroprevalence of T. cruzi infection, the sociodemographic profile of those infected and the characteristics that were significantly associated with CD. Furthermore, the study allowed us to benefit individuals with early diagnosis in the chronic phase of the infection, so that they can receive specialized care.